Flexible nonvolatile resistive switching memory devices based on Bi2Te3 nanosheets films. (13th December 2018) - Bao, Yongsheng; Ren, Zhiang; Li, Hongxing; Huang, Kai
Abstract: Flexible nonvolatile resistive switching memory is a promising candidate for next generation storage technologies. Exploring new materials is of crucial importance to achieve further performances of flexible nonvolatile resistive switching memory. In this work, topological insulator bismuth telluride (Bi2 Te3 ) nanosheets films were introduced into resistive switching memory devices firstly, a typical sandwich construction of Ag/Bi2 Te3 /indium tin oxide/polyethylene terephthalate with good flexibility, which exhibits nonvolatile bipolar resistive switching characteristics of operation voltage, good mechanical flexibility, and good storage stability. Furthermore, trap-controlled space charge limited current, thermionic emission are the dominant conduction mechanisms in the carrier transport. This work will provide an opportunity for Bi2 Te3 nanosheets to be used in flexible electronics application.